Factors Influencing the Risk Aversion in Vietnam: The Mediating Role of the Intention to Prevent COVID-19 - Vu Van Dong; Tran Nha Ghi; Nguyen Tan Trung; Tran Dang Khoa (Journal of Human, Earth, and Future, 2023)
The pandemic in Vietnam is increasingly escalating and spreading across provinces and cities. Therefore, Vietnam needs to implement preventive measures to control the spread of COVID-19. This study aims to examine the influencing factors, such as COVID-19 knowledge, behavior control, moral and subjective norms, the government's preventive e-guidelines, domestic social media, and environmental factors, on the intention to prevent COVID-19 and risk aversion. The study surveyed 201 Vietnamese citizens and utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to estimate path coefficients. The results indicate that COVID-19 knowledge, morals, and subjective norms positively impact the intention to prevent COVID-19 and risk aversion. The theoretical contribution of this study reveals that the intention to prevent the spread of COVID-19 partially mediates COVID-19 knowledge, moral and subjective norms, and risk aversion. Regarding practical implications, knowledge of COVID-19 transmission, symptoms, and preventive measures guided by healthcare experts and social networks (family, friends, and colleagues) is highly beneficial in Vietnam's efforts to combat the COVID-19 outbreak. Lastly, the study proposes some limitations and suggestions for further research.